Gastroprotective Activity of Ethanolic Extract of Trachyspermum Ammi Fruit - S. RAMASWAMY; S. SENGOTTUVELU; S. HAJA SHERIEF; S. JAIKUMAR; R. SARAVANAN; C. PRASADKUMAR; T. SIVAKUMAR (International Journal of Pharma and Bio Sciences, 2010)
Trachyspermum ammi fruit have traditionally been used in India as medicinal plant for the treatment of indigestion and dyspepsia and many other gastric disorders. In the present study ethanolic extract of Trachyspermum ammi fruit was used for investigation of antiulcer activity by using pylorus ligation, as anti-secretary model and Indomethacin induced ulcer model, ethanol induced ulceration model, cold restraint stress induced ulcer model as cytoprotective model. Animals pretreated with ethanolic extract of Trachyspermum ammi fruit at the dose 100mg/kg and 200mg/kg showed significant decrease in ulcer index and percentage ulcer protection in all models. The results suggests that the extract at 100mg/kg and 200mg/kg showed significant protection (p<0.001) by reducing ulcerative lesions when compared with control group of animals. These findings indicate that Trachyspermum ammi fruit extract shows significant antiulcer activity.